Cultural Context in English Student Textbook Talk Activefor the Tenth Grade Students (A Content Analysis) - Nurul Hasanah; Tahrun Tahrun; Mulyadi Mulyadi (ELTE Journal (English Languange Teaching and Education), 2018)
AbstractEnglish as a Foreign Language (EFL) has been introduced inseparably from its culture, either source culture, target culture, or international target culture. The integration of cultural contents in ELT (English Language Teaching) materials is strongly related to the current status of English. Being a global and common language, many recent theories suggest that the cultural contents of English materials should not be limited to native English speaking countries and should include local cultural contents. To this end, this research is intended at investigating the existence of cultural contents in an English textbook used by Senior High School students grade X in MAN 1 (Model) Lubuklinggau, entitled Talk Active. To this purpose, the media of cultural presentation, aspects of culture, categories of culture, and implications for language teaching were investigated. The method used in this study was content analysis. Some underlyingmodels proposed by Cortazzi and Jin (1999), Moran (2001), Yuen (2011), and Xiao (2011) were used as the main framework for analyzing the textbook. The investigation revealed that: (1) cultural contents were mostly presented through reading texts and pictures (56.5%) and (88.2%), (2) the dominant aspect of culture was products (33%), (3) the presented culture were mostly about source culture (30%), and (4) there were some strategies that can be applied that related to implications for language teaching. In summary, the exposures of visible cultural aspects of Indonesian culture which were presented through reading texts and pictures dominated the exposures of culture in Talk Active. Based on the findings, it is a need for textbook developers and teachers to provide a more balanced proportion of cultural contents in terms of the dimensions (products, persons, practices, perspectives) and categories of culture (source, target, and international target cultures) to help learners develop their intercultural understanding.Keywords: Language and Culture, Cultural Contents, English Textbook.